Existence and uniqueness of solutions for stochastic partial differential equations - LI Shangzhi (Journal of Shanghai Normal University (Natural Sciences), 2016)
In this paper the existence and uniquenessof solutions for two-dimensionalstochastic partial differential equations are investigated by means of successive approximations and Hölder nequality techniques. Moreover, our results are illustrated by an application to super Brownian Motion which is a non-Lipschitz problem.